P2X4 receptors (P2X4Rs) represent a novel target for the development of drugs to prevent and/or treat alcohol use disorders - Franklin, Kelle M.; Asatryan, Liana; Jakowec, Michael W.; Trudell, James R.; Bell, Richard L.; Davies, Daryl L. (Frontiers in Neuroscience, 2014)
Alcohol use disorders (AUDs) have a staggering socioeconomic impact. Few therapeutic options are available, and they are largely inadequate. These shortcomings highlight the urgent need to develop effective medications to prevent and/or treat AUDs. A critical barrier is the lack of information regarding the molecular target(s) by which ethanol (EtOH) exerts its pharmacological activity. This review highlights findings implicating P2X4 receptors (P2X4Rs) as a target for the development of therapeutics to treat AUDs and discusses the use of ivermectin (IVM) as a potential clinical tool for treatment of AUDs. P2XRs are a family of ligand-gated ion channels activated by extracellular ATP. Of the P2XR subtypes, P2X4Rs are expressed the most abundantly in the CNS. Converging evidence suggests that P2X4Rs are involved in the development and progression of AUDs. First, in vitro studies report that pharmacologically relevant EtOH concentrations can negatively modulate ATP-activated currents. Second, P2X4Rs in the mesocorticolimbic dopamine system are thought to play a role in synaptic plasticity and are located ideally to modulate brain reward systems. Third, alcohol-preferring (P) rats have lower functional expression of the p2rx4 gene than alcohol-non-preferring (NP) rats suggesting an inverse relationship between alcohol intake and P2X4R expression. Similarly, whole brain p2rx4 expression has been shown to relate inversely to innate 24 hr alcohol preference across 28 strains of rats. Fourth, mice lacking the p2rx4 gene drink more EtOH than wildtype controls. Fifth, IVM, a positive modulator of P2X4Rs, antagonizes EtOH-mediated inhibition of P2X4Rs in vitro and reduces EtOH intake and preference in vivo. These findings suggest that P2X4Rs contribute to EtOH intake. The present review summarizes recent findings focusing on the P2X4R as a molecular target of EtOH action, its role in EtOH drinking behavior and modulation of its activity by IVM as a potential therapy for AUDs.